Beverage Consumption Habits around the World: Association with Total Water and Energy Intakes - Lluis Serra-Majem (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Fluid intake has barely been assessed, and hydration status has only rarely been measured in epidemiological studies. This hampers attempts to assess the adequacy of water intake at a population level. However, although guidelines have been established to determine how much water humans require to avoid dehydration and to optimize physical and psychological function, limited data are available on the total water and beverages intake. Therefore, the percentage of population with inadequate water intake is unknown. There is a clear need for studies in different settings around the world that quantify total water and beverage intake and explore associations between types of beverages consumed and energy intake.